2023
DOI: 10.21203/rs.3.rs-1808277/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ATPergic signaling disruption in human sepsis as a potential source of biomarkers for clinical use

Abstract: Sepsis is a life-threatening organ dysfunction caused by a dysregulated inflammatory response to infection. To date, there is no specific treatment established for sepsis. In the extracellular compartment, purines such as adenosine triphosphate (ATP) and adenosine play essential roles in the immune/inflammatory responses during sepsis and septic shock. The balance of extracellular levels among ATP and adenosine are intimately involved in the signals related to immune stimulation/immunosuppression balance. Spec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
(2 reference statements)
2
1
2
Order By: Relevance
“…In contrast to disparate results with regard to ATP levels between our two studies (current and reference [36]), both of our studies find comparable adenosine levels in septic and control patients. This, however, is inconsistent with results from other studies, in which adenosine levels were higher in septic patients than in controls (37,38).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to disparate results with regard to ATP levels between our two studies (current and reference [36]), both of our studies find comparable adenosine levels in septic and control patients. This, however, is inconsistent with results from other studies, in which adenosine levels were higher in septic patients than in controls (37,38).…”
Section: Discussioncontrasting
confidence: 99%
“…We initially determined the levels of some of the major extracellular purines and found that ATP levels were decreased in septic patients when compared with healthy individuals, whereas no differences were noted for UTP, UDP, and adenosine. This finding of decreased ATP levels was surprising, because in a previous study conducted in a different medical center, we observed increased circulating ATP concentrations in septic patients (36). The current results also differed from our previous ones in that ATP levels in the current study were in the mid-nanomolar range, whereas in the previous one, they averaged 5 to 10 μM.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Another significant source of ADP is the secretion from platelet dense granules upon activation; it promotes platelet aggregation via a positive feedback mechanism by binding to ADP receptors on the same and other circulating platelets (Remijn et al, 2002). In a recent study, Leite et al (2022) found that on the first morning following intensive care unit admission, at the early onset of sepsis, serum ADP levels and ADPase activity were higher (about 18 and 1.6 times, respectively) when compared with control patients. They proposed that serum levels of ADP and ADPase activity may be associated with the diagnosis of sepsis and may represent potential biomarker candidates.…”
Section: The P2y12 Receptormentioning
confidence: 96%